Columns in analytical-scale supercritical fluid chromatography: From traditional to unconventional chemistries - Plachká, Kateřina; Pilařová, Veronika; Horáček, Ondřej; Gazárková, Taťána; Vlčková, Hana Kočová; Kučera, Radim; Nováková, Lucie (Journal of separation science, 2023)
Within this review, we thoroughly explored supercritical fluid chromatography (SFC) columns used across > 3000 papers published from the first study carried out under SFC conditions in 1962 to the end of 2022. We focused on the open tubular capillary, packed capillary, and packed columns, their chemistries, dimensions, and trends in used stationary phases with correlation to their specific interactions, advantages, drawbacks, used instrumentation, and application field. Since the 1990s, packed columns with liquid chromatography and SFC-dedicated stationary phases for chiral and achiral separation are predominantly used. These stationary phases are based on silica support modified with a wide range of chemical moieties. Moreover, numerous unconventional stationary phases were evaluated, including porous graphitic carbon, titania, zirconia, alumina, liquid crystals, and ionic liquids. The applications of unconventional stationary phases are described in detail as they bring essential findings required for further development of the supercritical fluid chromatography technique.
Keywords: chiral stationary phases; unconventional stationary phases; packed columns; capillary columns; supercritical fluid chromatography